Antifreeze Solutions in Home Fire Sprinkler Systems - Consultants, Inc., Code.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
None.
I Introduction -- II Background -- III Phase II Test Plan and Setup -- IV Phase II Test Results -- V Analysis -- VI Future Research and Recommendations -- VII Summary.
Keywords: Engineering; Chemicals -- Safety measures; System safety; Civil engineering; Engineering; Civil Engineering; Quality Control, Reliability, Safety and Risk; Safety in Chemistry, Dangerous Goods